INTRODUCING THE CONCEPT OF NUMBERS AS PART OF SPEECH IN ELEMENTARY GRAMMAR AND SPELLING TEACHING - Medojević, Iva (Metodička teorija i praksa, 2024)
In the context of language practice and linguistic science, numbers as a part of speech occupy a significant place in the grammatical, more precisely, in the morphological system. The aim of this study was to examine the role of numbers in primary education and, based on that, suggest the direction in which its further development could progress. Existing knowledge within the framework of linguistic sciences was presented, and the research encompassed an analysis of content and a comparative analysis, including both old and new curricula from the first to the fourth grade, current programs from the fifth grade of elementary school to the fourth grade of gymnasium, as well as grammar textbooks from the second to the fifth grade of elementary school. Upon analyzing available literature, it was concluded that there is no consensus in the scientific community at multiple levels: some authors do not recognize numbers as a part of speech, and various classifications and characteristics of this type of word are mentioned. Additionally, based on content analysis, similar contradictions were observed, including inconsistencies in the didactic-methodological apparatus of different textbooks, and the fact that a clear and logical connection between the content of the first and second cycles of primary education and upbringing, as well as between primary and secondary school, has not been established. These findings suggest the need for changes that will overcome these inconsistencies, both at the level of program content and the content of grammar textbooks. This would ensure education grounded in linguistic science and adapted to the age and developmental needs of elementary school students.
Keywords: elementary grammar and spelling teaching; numbers; school curricula; grammar textbook; didactic-methodological apparatus